Justice without borders : cosmopolitanism, nationalism, and patriotism - Tan, Kok-Chor, 1964- (Contemporary political theory., 2004)
Kok-Chor Tan argues that the cosmopolitan idea of global justice may be understood in such a way that it can accept some forms of nationalist and patriotic commitments without having to abandon its ideal of global equal concern. This accessible, persuasive book will appeal to political theorists and moral philosophers.